2013
DOI: 10.1128/jcm.01299-12
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a New Community Genotype Methicillin-Resistant Staphylococcus aureus Clone That Is Unrelated to the USA300 Clone and That Causes Pediatric Infections in Colombia

Abstract: dThe dissemination of a clone of community genotype methicillin-resistant Staphylococcus aureus (CG-MRSA) that is related to USA300 has been reported in Latin America. We recently detected isolates of a new clone of CG-MRSA (spa type t1635 and ACME-negative) that was genetically unrelated to the USA300 clone and that causes infections in children in Colombia. This finding indicates the appearance of a new clone of CG-MRSA in our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…The molecular characterization of the 32 CG-MRSA isolates demonstrated that they all harboured SCC mec IVa (IV.1.1.1), were of spa type t1635 (YHGFMBO) and presented a 54-bp insertion in the sausa300_0808 gene in S. aureus pathogenicity island 5 (SaPI5). These same features were previously found in the COL923 isolates recovered from paediatric infections in Bogota, Colombia [ 13 ]. All isolates harboured the sek and seq genes within SaPI5.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The molecular characterization of the 32 CG-MRSA isolates demonstrated that they all harboured SCC mec IVa (IV.1.1.1), were of spa type t1635 (YHGFMBO) and presented a 54-bp insertion in the sausa300_0808 gene in S. aureus pathogenicity island 5 (SaPI5). These same features were previously found in the COL923 isolates recovered from paediatric infections in Bogota, Colombia [ 13 ]. All isolates harboured the sek and seq genes within SaPI5.…”
Section: Resultssupporting
confidence: 85%
“…This particular region contains an ORF that encodes a putative transposase. Although the SCC mec IVa element in the COL923 clone still has high nucleotide identity (>98%) with the SCC mec IVa element in the USA300 clone, our results show that it has also acquired certain foreign DNA fragments [ 12 , 13 ]. These results reinforce the idea that the new variant (COL923) has gained DNA fragments and support the importance of further studies aimed at increasing our understanding of this process.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…La diseminación de aislamientos SASM-USA300 y su probable capacidad de adquirir SCCmec puede estar contribuyendo al aumento de la frecuencia de infecciones causadas por el clon SARM-USA300, reportado en nuestro país en el 2006 y que ya es causante de aproximadamente 94 y 60 % de las infecciones en población pediátrica y de adultos, respectivamente (8,10,45,46 Es necesario seguir el estudio de este fenómeno y profundizar en el posible origen de nuestros aislamientos SARM para llevar a cabo la vigilancia epidemiológica y los estudios clínicos no solo de los SARM sino de los SASM, pues en muchas ocasiones se subestiman debido a que su tratamiento antibiótico es mucho más fácil y efectivo, pero podrían ser el reservorio de aislamientos más patógenos y virulentos como se ha descrito con relación al USA300.…”
Section: Discussionunclassified